2021
DOI: 10.2337/db21-0205
|View full text |Cite
|
Sign up to set email alerts
|

VDR/Atg3 Axis Regulates Slit Diaphragm to Tight Junction Transition via p62-Mediated Autophagy Pathway in Diabetic Nephropathy

Abstract: Supplemental Figure 1. The average content of ZO-1 experienced an increasing trend in DN patients with the pathological progression from stage IIa to IV. The ratio of IOD of ZO-1 (A) and p62 (B) to WT-1 count in the glomeruli of DN patents at different stages as indicated.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Autophagy has been shown to be essential to the maintenance of cellular homeostasis in podocytes [26, 27]. Emerging evidence has suggested that dysregulated autophagy may contribute to both glomerular and tubulointerstitial pathologies in the kidneys of DKD [17, 28, 29]. Recent studies have also revealed that vitamin D-vitamin D receptor regulates defective autophagy in renal tubular epithelial cells and podocytes [13, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been shown to be essential to the maintenance of cellular homeostasis in podocytes [26, 27]. Emerging evidence has suggested that dysregulated autophagy may contribute to both glomerular and tubulointerstitial pathologies in the kidneys of DKD [17, 28, 29]. Recent studies have also revealed that vitamin D-vitamin D receptor regulates defective autophagy in renal tubular epithelial cells and podocytes [13, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression levels of P53 and miR-214 negatively correlated with the expression levels of ULK1 in those patients (Figure 2) [67]. Interestingly, Wang et al revealed that ineffective autophagic flux prevents P62-dependent degradation of zonula occludens-1 (ZO-1), a tight junction protein, and accelerates slit diaphragm replacement by tight junction in podocytes, causing foot process effacement [72].…”
Section: Sestrin2 Improves Autophagy In Diabetic Nephropathymentioning
confidence: 97%
“…Given the reciprocal interaction of NLRP3 and autophagy and the role of dysregulated autophagy in the pathogenesis of DKD, we considered that the interaction between Nlrp3 and autophagy factors may be a potential mechanism by which Nlrp3 in podocytes exerts additional effects independent of caspase-1. [34][35][36] To examine whether glomerular autophagy is differentially regulated by Nlrp3 and caspase-1 in diabetic mice, we determined glomerular levels of autophagy markers LC3II/LC3I and p62 (sequestosome 1) in diabetic Nlrp3 V-pod , diabetic Nlrp3 KO-Pod , and diabetic Casp1 KO-Pod glomeruli by immunoblotting. Consistent with other reports, autophagy was impaired in diabetic glomeruli of wild-type mice (Pod-Cre ), as reflected by a decreased LC3II/LC3I ratio and increased p62 levels (Figure 7a-c).…”
Section: Podocyte-specific Nlrp3 Deficiency But Not Caspase-1 Deficie...mentioning
confidence: 99%